Horizontal ECG in acute anterolateral myocardial infarction - KEPEZ, ALPER; ERDOĞAN, OKAN (SPRINGER WIEN, 2016)
The present study aims to compare the amount of ST segment changes recorded by horizontal electrocardiography (hECG) with standard ECG (sECG) in patients with acute anterior and/or lateral ST segment elevation myocardial infarction (STEMI). Consecutive eligible patients (n = 58) who were diagnosed with acute anterior and/or lateral STEMI were included in the study. After recording simultaneous sECG and hECG by placing precordial leads (V3-6) horizontally on the left 4th intercostal space, ST segment changes were compared. The mean ST segment changes (mV) on hECG were significantly higher than sECG in V-4 (0.27 +/- 0.2 vs. 0.21 +/- 0.21, p = 0.001), V-5 (0.21 +/- 0.17 vs. 0.12 +/- 0.16, p < 0.001) and V-6 (0.09 +/- 0.1 vs. 0.04 +/- 0.12, p < 0.001), respectively. When hECG and sECG were compared in patients with BMI < 30 kg/m(2), mean ST segment changes (mV) on hECG were significantly higher than sECG in V-4 (0.29 +/- 0.21 vs. 0.21 +/- 0.24, p = 0.004), V-5 (0.22 +/- 0.19 vs. 0.13 +/- 0.17, p < 0.001) and V-6 (0.11 +/- 0.11 vs. 0.04 +/- 0.11, p < 0.001), respectively. Mean ST segment changes in patients with anterior and/or lateral STEMI were significantly higher and easily detectable on hECG compared with sECG. We suggest that hECG be used in conjunction with sECG to diagnose anterior and lateral wall STEMI in cases of diagnostic doubt.
Keywords: ECG; ST segment elevation; Acute myocardial infarction; Diagnosis; Body surface mapping; 12-LEAD ELECTROCARDIOGRAM; LEADS